Uji Efikasi Rodentisida Nabati Daun Ruku-Ruku (Ocimum sanctum L.) Terhadap Mortalitas Tikus Sawah Rattus rattus argentiventer Robb & Kloss. di Laboratorium - Sinaga, Christine Nofriaeti Lusiana (2016)
The objective of the research was to know efficacy of botanical rodenticides ruku-ruku’s leaves for mortality of rice field rat. The research is held in Laboratory Vertebrate Pest Control Balai Besar Perbenihan dan Proteksi Tanaman Perkebunan (BP2TP) from December-Pebruary 2016. The method used was Randomized Complete Design non factorial. Parameter observed were body weight of rats, bait consumption, mortality percentage, behaviour of rats. The result showed that ruku-ruku’s leaves affected reduction in body weight of R. rattus argentiventer. The highest bait consumption was showed on P3 (19,93%) and the lowest P0 (13,67%) on first day after application. The highest mortality percentage was showed on P3 (16,67%) and the lowest was showed on P0 (0,00%) on day eighteen after application. Behaviour of rats rest (46,64%), shiver (15,06%), along the floor (13,87%), biting cage (8,39%), bitting food/water box (6,75%), repeat salto (5,79%), lack of appetite (1,86%), tidak inactivity (0,98%), dan bleeding on eye/nose (0,66%). 093011131